Identity and transformation within the Playhouse Dance Company, 1993-1997 - Ballantyne, Tammy Marguerite (Rhodes University, Faculty of Humanities, Department of Drama, 1998)
This thesis examines the principles and policies underlying the need for transformation within the Playhouse Dance Company (PDC) in Durban and the actualities of implementing these visions and procedures. It is proposed that artistic structures, ideals and processes cannot remain impervious to the climate of change. Alterations in the political arena demand radical permutations within arts councils and their concept of repertoire, educational programmes and training. Transformation is linked to the problem of identity and it is suggested that the company is in the midst of a journey towards "becoming" rather than "being". Chapter One comprises an overview of changing trends in the arts globally and the impact on South Mrican art forms and processes. There is also an examination of the past, the establishment of arts councils and the colonial heritage of the dance companies within these councils. The formative years of the NAP AC Dance Company and the strategies formulated by former artistic directors have, it is suggested, hampered the transformation process. Chapter Two focuses on the PDC's endeavours to transform between the years 1993 and 1997. Lack of funding, conservative public tastes and training processes are. all' issues confronting management, choreographers, educators and performers in attempting to provide a clear direction towards transformation. The company walk a tightrope as they struggle to balance the heritage of their artistic past while giving birth to a new heritage for the future. Chapter Three discusses two areas that reveal measurable attempts at transformation. Hawkins offers re-inventions of the classics which encourages innovation, and Siwela Sonke was conceived to draw on dance forms located in Kwazulu-Natal in the search for a South Mrican dance aesthetic. Chapter Four investigates whether transformative visions are becoming a reality and suggests how the company could extend the process further. This chapter concludes with .. ideas about the nature of culture and how this informs,the exercise of transformation. This thesis proposes that transformation within the PDC is occurring even though it has its shortcomings. The main thrust of the research is to investigate, identifY and document factors that are contributing to current dance trends in Durban.
Keywords: Playhouse dance company; Dance -- South Africa